2015
DOI: 10.1007/s10147-015-0917-1
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis on the utility and complications of upper arm ports in 433 cases at a single institute

Abstract: BackgroundWe have employed upper arm central venous ports (UACVPs) since 2006 for long-term intravenous chemotherapy (CTx) or fluid supplementation. We evaluated the long-term availability of CVPs implanted in the upper arm to determine whether UACVPs could be one of the treatment options besides chest CVPs in terms of CVP-related complications.MethodsWe reviewed the medical records of all patients who underwent subcutaneous implantation of UACVPs at Kyoto University Hospital from 1 April, 2006 to 30 June, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
(30 reference statements)
3
36
0
Order By: Relevance
“…22 In this study, articles that evaluated this place of insertion regarding the risk of infections were not included. , catheter-related infection 9,11,16 and infection of the subcutaneous pouch 20 were the most prevalent infections in the studies, with a predominance of gram-negative bacteria, such as Staphylococcus aureus 12,14,16,19,20 and Sthaphylococcus epidermis. 16,20 In most cases, the catheter had to be removed and the causative agent had to be removed.…”
Section: 2013mentioning
confidence: 97%
See 2 more Smart Citations
“…22 In this study, articles that evaluated this place of insertion regarding the risk of infections were not included. , catheter-related infection 9,11,16 and infection of the subcutaneous pouch 20 were the most prevalent infections in the studies, with a predominance of gram-negative bacteria, such as Staphylococcus aureus 12,14,16,19,20 and Sthaphylococcus epidermis. 16,20 In most cases, the catheter had to be removed and the causative agent had to be removed.…”
Section: 2013mentioning
confidence: 97%
“…11,13 In one, the types of treatment by adjuvant and neoadjuvant chemotherapies were compared and it was noticed that treatment by neoadjuvant chemotherapy is associated with a higher risk of infection. 13 Regarding the other study, chemotherapy was compared to intravenous infusion of fluids in order to identify which solution presented the greatest risk for the development of infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one 7,8,20,22,25,36,39,41,42,48,55,61,64,68,69,71,75,76,92,94,95 of the 69 noncomparison studies (23 cohorts, n = 12 265) reported VTE by number of thrombosis per 1000 catheter-days. Within these studies, the pooled rate of VTE was 0.08 (95% CI: 0.06-0.10) per 1000 catheter-days ( Figure S2).…”
Section: The Incidence Of Tivap-related Vtementioning
confidence: 99%
“…1 The indwelling device not only serves as a secure vascular access point for parenteral medications, but also reduces the risks of repeat venipuncture. However, catheter-related complications, such as fracture, [2][3][4][5][6][7] malfunction, 8-10 migration, [11][12][13] catheter related thrombosis, 3 and infection 3,14,15 have been widely reported in the literature, with the rate of complications ranging from 1.8 to 33.95%. All available conventional ports mount the catheter via the connecting tube, with the possibility of mal-assembly leading to catheter flaring and inappropriate nut loading.…”
Section: Introductionmentioning
confidence: 99%